2016
DOI: 10.1152/ajpheart.00681.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sex-dependent myocardialS-nitrosothiol proteome

Abstract: Premenopausal women exhibit endogenous cardioprotective signaling mechanisms that are thought to result from the beneficial effects of estrogen, which we have shown to increase protein S-nitrosylation in the heart. S-nitrosylation is a labile protein modification that increases with a number of different forms of cardioprotection, including ischemic preconditioning. Herein, we sought to identify a potential role for protein S-nitrosylation in sex-dependent cardioprotection. We utilized a Langendorff-perfused m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 53 publications
11
41
0
Order By: Relevance
“…Increase in ADMA concentration seems to be an independent predictor of acute coronary events and cardiovascular mortality [Valkonen et al, 2001]. Our results confirm the results of a recent study that characterized the mitochondrial proteome and identified increased eNOS expression in hearts of female C57BL/6J mice [Shao et al, 2016]. This and the reduced ADMA levels we observed are interesting, since other studies provide further support for sexdependent cardioprotection [Murphy et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…Increase in ADMA concentration seems to be an independent predictor of acute coronary events and cardiovascular mortality [Valkonen et al, 2001]. Our results confirm the results of a recent study that characterized the mitochondrial proteome and identified increased eNOS expression in hearts of female C57BL/6J mice [Shao et al, 2016]. This and the reduced ADMA levels we observed are interesting, since other studies provide further support for sexdependent cardioprotection [Murphy et al, 2011].…”
Section: Discussionsupporting
confidence: 90%
“…This is suggestive of a cardioprotective role for estrogen, but recent hormone replacement therapy trials in postmenopausal women have failed [46, 47]. In animals model of I/R injury (i.e., mouse, rat), female hearts display similar intrinsic protection from injury as we and others have shown [1619, 2224, 35, 39, 48]. Studies have also shown that exogenous estrogen protects both male and female hearts from I/R injury in a number of species, including mouse and rabbit [35, 49, 50].…”
Section: Discussionmentioning
confidence: 67%
“…This has been attributed to sex differences in the activity of ATP-dependent potassium channels [33], the mitochondrial permeability transition pore [34], and differences in nitric oxide-dependent cardioprotective signaling pathways [35]. In addition, estrogen is known to protect the heart from ischemic injury [3637].…”
Section: Discussionmentioning
confidence: 99%